Analisis Kegagalan Sebuah Poros Engkol Bekas Mesin Diesel Generator untuk Kapal - Khaeroman Khaeroman; Susanto Susanto (Jurnal Maritim Polimarin, 2018)
This research discusses the failure of the diesel engine crankshaft of four stroke 6 cylinder, which is used in diesel generators of marine vessels. A correct analysis of crankshaft conditions is essential to prevent crankshaft fracture failures and cracks. Crankshaft deformed due to misalignment of the main journaling bearings. The purpose of this research is to determine the safe limit of the feasibility of a crankshaft to the damage that occurs on the surface of the crank pin journaling and steps to prevent the occurrence of failure on the crankshaft. This article presents the results of crankshaft failure analysis by material testing method through metallurgical test and hardness test. The test material taken was part of the crank pin journaling on cylinder number 3 which experienced by worn-out abnormality, while the test material from the crank pin section of the journal of cylinder number 5 was as a comparison with the normal surface condition. The result of chemical composition test of crankshaft is included in AISI 4140 classification. While the hardness value on crank pin surface of journal of cylinder number 3 is below the predetermined hardness value. Micro structure on cylinder no. 3 has an irregular spherical grain shape and the phase is pearlit (ferrit and cementit) in which the pearlit has a soft and also a hard nature.